Platelet Coagulant Activities and Clinical Severity in Haemophilia - Walshi, Peter N.; Rainsford, S. G; Biggs, Rosemary (Thrombosis and Haemostasis, 1973)
Assays for platelet coagulant activities concerned with the initiation and progress of intrinsic coagulation were done pair-wise in two groups of 16 haemophiliacs without detectable factor VIII. The patients in the ‘severe’ group had experienced 7.9-22.8 (mean 13.7) spontaneous haemorrhages per 100 days during an average of 431 days of observation, whereas those in the ‘mild’ group had bled 0-5.5 (mean 3.2) times per 100 days during an average of 282 days of observation. Contact product forming activity, collagen-induced coagulant activity and intrinsic factor-Xa forming activity were decreased in the severely-affected group and increased in the mildly affected group, whereas there was no great difference in platelet factor 3 activity between the two groups. Variations of platelet coagulant activities concerned with the initiation and early stages of intrinsic coagulation may influence clinical severity in haemophilia.